Comparison of gene expression and activation of transcription factors in organoid-derived monolayer intestinal epithelial cells and organoids. Issue 10 (23rd July 2021) - Takahashi, Yu; Inoue, Yu; Kuze, Keitaro; Sato, Shintaro; Shimizu, Makoto; Kiyono, Hiroshi; Yamauchi, Yoshio; Sato, Ryuichiro
ABSTRACT: Intestinal organoids better represent in vivo intestinal properties than conventionally used established cell lines in vitro . However, they are maintained in three-dimensional culture conditions that may be accompanied by handling complexities. We characterized the properties of human organoid-derived two-dimensionally cultured intestinal epithelial cells (IECs) compared with those of their parental organoids. We found that the expression of several intestinal markers and functional genes were indistinguishable between monolayer IECs and organoids. We further confirmed that their specific ligands equally activate intestinal ligand-activated transcriptional regulators in a dose-dependent manner. The results suggest that culture conditions do not significantly influence the fundamental properties of monolayer IECs originating from organoids, at least from the perspective of gene expression regulation. This will enable their use as novel biological tools to investigate the physiological functions of the human intestine. Graphical Abstract: